Welfare and vulnerability in Tajikistan: Evidence from twelve districts in Khatlon Province, 2015–2023 - Lambrecht, Isabel B.; Pechtl, Sarah; Mardonova Tolibkhonovna, Mohru; Akramov, Kamiljon T. (International Food Policy Research Institute, 2023)
Household survey data from February-March 2023 and February-March 2015 were analyzed to document changes in welfare of households in twelve districts of Khatlon Province, USAID’s Zone of Influence (ZOI), over the last eight years. Key findings: • Housing conditions improved, indicating improved living conditions. Only 1 percent of households had improved sanitation in 2015, but nearly half (49 percent) of all households did so in 2023. • Total consumption expenditures on food, non-food, and durables increased nearly 10 percent (in real terms) between 2015 and 2023 • Expenditures on food increased, but these were used to purchase more expensive food rather than improving dietary quality. This led to a stagnation in diet diversity among women of which 70 percent have inadequate dietary diversity. Household consumption patterns do show improvements over time. • Poverty declined by about 10.4 percent, but movements of households in and out of poverty between 2015 and 2023 suggest that a significant share of households are at risk of falling back into poverty in the face of adversity. • Correlates with consumption expenditures and poverty demonstrate that households with more household members, with fewer livelihood sources, and in more remote locations are worse off. Households with more women are more likely to be poor given women’s limited income generating opportunities. • Households that participated in agricultural development activities were approximately 12.7 percent less likely to be poor than other households. Recommended actions The findings underscore the importance of the priorities specified in the Government of Tajikistan’s Agri-Food System and Sustainable Development Program (ASDP), specifically strategic priority 4 on food security and safety, and motivate the following policy recommendations: • Continue to support healthy diets through improved access to food as well as behavior change communication related to dietary diversity and consuming healthy food. • Further research should serve to understand pathways to lifting farmers out of poverty, including analyzing what works and why when implementing agricultural interventions. • Continued efforts are needed to mitigate women's disproportionate susceptibility to poverty and their vulnerability to poverty-induced outcomes.